Evaluasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan di Kecamatan Nanggulan Kabupaten Kulon Progo - Gentur Wiku Pribadi; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Various problems in public service often found in its implementation although standards and the regulations have been settled .Various these problems in between other about timeliness of service , the cost of service , and resources supporting the provision of the service .Of the existing problems, the government tried to bring up a innovation in the field of public services through policy. These various problems are about the timeliness of service, the cost of service, and resources supporting the provision of the service. Of the existing problems, the government tried to bring up an innovation in the field of public services through Policy of District Integrated Administration Services that arranged in affairs regulation no. 4 years 2010, that contain changing authority regent to the related sub-district. Follow up the government affairs regulation, District of Kulon Progo through Bupati Regulation no. 64 years 2012 about Standard of Public Service on District, implement the integrated administration services on district in all of the district in Kabupaten Kulon Progo including in Nanggulan District. In its implementation in Nanggulan District, there are various obstacles as deficiency of personnel implementing, facilities and infrastructures , also the target of about the time and the cost of services that have not been in full .Technique of data collection use an depth interview technique and study documents .The results of the study showed that the implementation viewed from the cost of serviceaspect, it was sufficient and from the aspect of service period and resources supporting the provision of the service is inadequate. The purpose of integrated administration services in district has yet to be reached maximally because of changing authority given is not effective and efficient created quality services and the closer to the community. The advice that provided are the government in Kabupaten Kulon Progo and Nanggulan District increase the supporting facilities service and improve the method of service so the time of the service was better; and review of the changing authority given to head to achieve policy aims to be maximum.